KOLABORASI AKTOR PADA PENANGANAN KEKERASAN TERHADAP PEREMPUAN DI KABUPATEN ACEH TAMIANG - Jayanti Sari; Neni Sriwahyuni; Susniwati Susniwati (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
Women are still afraid to voice the violence that happened to them and choose to remain silent.Violence against women also occurred in Aceh Tamiang District with various forms of violenceexperienced by them. The purpose of this study is to analyze violence against women in Aceh TamiangDistrict. The research method used is qualitative with purposive selection of informants and datacollection techniques through observation, interviews, and documentation. The results of the studyfound that the communication built by the Village Community Empowerment Service, Women’sEmpowerment and Family Planning was still lacking. Added value is public value, which is the resultof efficiency, democracy in institutions, and collaboration processes. There is a deliberation processwhich is a collaboration that forms mutual learning, building communities and employing interactive.In addition, it was found the importance of academic involvement in providing opportunities forwomen victims of violence to continue their education to a higher level.